Jerome and the Monastic Clergy: A Commentary on Letter 52 to Nepotian, with an Introduction, Text, and Translation. By Andrew Cain - White, Carolinne (The journal of theological studies, 2014)
Cain’s commentary on Jerome’s Letter 52 to Nepotian is one of two published by him in 2013, the other being a commentary on Jerome’s epitaph on Paula (Letter 108). Letter 52 is a relatively short work of 17 sections, the text and translation of which are given in this volume, together with an introduction, a list of modern bibliographical references, the commentary itself, a bibliography of ancient authors, and finally indexes of names and subjects, of sources, and of those Latin, Greek, Hebrew, and Aramaic words discussed in the commentary., Current scholarship agrees that Jerome wrote the letter from Bethlehem in 393. The addressee, Nepotian, was a young priest at Altinum in north-western Italy, where his uncle, Heliodorus, a friend of Jerome since their student days in Rome, was bishop.